2017
DOI: 10.3386/w23865
|View full text |Cite
|
Sign up to set email alerts
|

Should Flavors be Banned in E-cigarettes? Evidence on Adult Smokers and Recent Quitters from a Discrete Choice Experiment

Abstract: E-cigarettes are available in over 7,000 flavors, whereas all flavors but menthol are banned in combustible cigarettes. The FDA recently requested a ban on e-cigarette flavors, but was rejected. The FDA is again considering this ban and also a ban on menthol in combustible cigarettes, but there is little information on the impacts of alternative bans on the market for combustible and ecigarettes. Our study provides these much-needed estimates. We conduct a discrete choice experiment on a nationally representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…The DCE is a method used to elicit causal effects of attributes on product choices [37]. DCEs are used in tobacco research [9], including e-cigarettes [10][11][12][13][14][15]. In this paper, the DCE was used to elicit preferences for tobacco products which were described by their attributes.…”
Section: Discrete Choice Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCE is a method used to elicit causal effects of attributes on product choices [37]. DCEs are used in tobacco research [9], including e-cigarettes [10][11][12][13][14][15]. In this paper, the DCE was used to elicit preferences for tobacco products which were described by their attributes.…”
Section: Discrete Choice Experimentsmentioning
confidence: 99%
“…This study used an online discrete choice experiment (DCE) to examine trade-offs of young adults across cigarettes and e-cigarettes and key policy-relevant attributes. The DCE approach enabled gathering of preference data in advance of a regulatory decision, which is useful for informing policy prior to implementation [9][10][11][12][13][14][15][16]. Other approaches used experimental markets [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Given the evidence above, it is likely that regulation that limits the diversity of available ENDS products with respect to flavor and nicotine content will also have an effect on ENDS appeal and use (Pacek, Wiley, et al, 2019). For instance, within the context of hypothetical choice tasks among people who use both ENDS and cigarette, restricting the available flavors of ENDS (Buckell et al, 2017; Pacek, Rass, et al, 2019), as well as restricting the availability of desired ENDS nicotine contents (Pacek et al, 2018), has been found to increase the likelihood of participants’ choosing to decrease their use of ENDS. Survey data collected among a sample of young adults following the implementation of a comprehensive tobacco product flavor ban in San Francisco, California indicated that the overall prevalence of flavored tobacco use as well as flavored ENDS use decreased, but was not eliminated (Yang et al, 2020).…”
mentioning
confidence: 99%
“…A flavor ban on ENDS should reduce youth vaping, a concern in many countries. But the Buckell et al (2017) study found that this was not the case for adult smokers; that a comprehensive flavor ban on ENDS and a menthol ban on cigarettes would increase cigarette demand among US smokers, encourage the switch back to cigarettes and yield only small (3%), incremental abstinence from ENDS and cigarettes. Some studies have found that cigarettes and ENDS are substitutesage restrictions on ENDS increase adolescent cigarette smoking (Friedman, 2015;Pesko et al, 2016a andDave et al, 2019a).…”
Section: Government Interventions and Regulations On E-cigarettes (Electronic Nicotine Delivery Systems)mentioning
confidence: 99%